2020
DOI: 10.1002/gcc.22903
|View full text |Cite
|
Sign up to set email alerts
|

PARP inhibition in prostate cancer

Abstract: Defects in DNA damage repair genes are more common in prostate cancer than previously thought. These alterations provide an opportunity for precision oncology approaches and a number of studies have now shown that PARP inhibitors can have significant antitumor activity in men with DNA damage repair‐deficient metastatic castration‐resistant prostate cancer. This review summarizes the key clinical trials related to the use of PARP inhibitors in prostate cancer. Besides clinical outcomes, toxicity, and PARP inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
(92 reference statements)
1
5
0
Order By: Relevance
“…Other major cancer types where PARP inhibitors and combinatorial therapies are being developed and recent trials showed encouraging results include breast, pancreatic and prostate cancer. Reviews by Ali et al, 37 Singh et al 38 and Nientiedt et al 39 thoroughly describe recent clinical and diagnostic data in these cancer types and provide an outlook on future developments. Future clinical trials will show whether this therapeutic approach can be extended to other cancer types, possibly also in conjunction with other therapies including checkpoint blockers 40 .…”
Section: Figurementioning
confidence: 99%
“…Other major cancer types where PARP inhibitors and combinatorial therapies are being developed and recent trials showed encouraging results include breast, pancreatic and prostate cancer. Reviews by Ali et al, 37 Singh et al 38 and Nientiedt et al 39 thoroughly describe recent clinical and diagnostic data in these cancer types and provide an outlook on future developments. Future clinical trials will show whether this therapeutic approach can be extended to other cancer types, possibly also in conjunction with other therapies including checkpoint blockers 40 .…”
Section: Figurementioning
confidence: 99%
“…Olaparib (Lynparza) is a small, oral, and bioavailable molecule that selectively binds and inhibits PARP [162] . Mateo et al [134] published two Phase II clinical trials, "TOPARP-A" (NCT01682772) and "TOPARP-B" (NCT01682772), involving patients with mCRPC who had previously received standard treatments and who were treated with olaparib.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…Both studies demonstrated that patients with defective DDR genes and who were no longer responding to the current treatments exhibited a high response rate to olaparib. Importantly, response to treatment seemed dependent on specific DDR gene defects, as the highest response was achieved in the BRCA1/2 aberrant subgroup [ 133 , 134 , 163 ] .…”
Section: Emerging Treatments Targeting Mcrpcmentioning
confidence: 99%
“…Although the mechanisms underlying tumor cell migration and invasion have been extensively studied [4], relatively little is known about whether, and to what extent, recurrent genetic alterations modulate these activities. In prostate cancer, there is compelling evidence that mutations in genes involved in the homologous recombination-mediated repair (HRR) of DNA double-strand breaks, most notably BRCA2, define a subset of patients with a therapeutic vulnerability to PARP inhibition and platinum compounds [5][6][7]. This subgroup of men with prostate cancer also shows distinct clinical characteristics, including a higher rate of lymph node and distant metastasis and poorer patient survival outcomes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%